(untitled) (Medicine Today, 2014)
Drug abuse has reached epidemic proportions in many countries including Bangladesh and threatens to overwhelm economic, social, and health care systems. In addition to their effects on the central nervous system, many of these agents induce profound changes in the heart and circulation that are responsible for a significant proportion of drug-related morbidity. Drugs that can affect the cardiovascular system are cocaine, heroin, inhalants, ketamine, lysergic acid diethylamide(LSD), marijuana,3,4-methylenedioxymethamphetamine(MDMA), methamphetamine, nicotine, phencyclidine (PCP), prescription stimulants, steroids .This article reviews the cardiovascular problems associated with drug abuse. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17928 Medicine Today 2013 Vol.25(2): 90-92